Spiritual Well being of Breast Cancer Patients Undergoing Chemotherapy through Mindfulness Based Spiritual - Fefi Eka Wahyuningsih; Muchlis Achsan Udji Sofro; Meidiana Dwidiyanti (Media Keperawatan Indonesia, 2019)
Breast cancer patients newly diagnosed and undergoing chemotherapy experience physical and emotional changes. Patients experience stress due to side effects of chemotherapy drugs, financial changes, self-perceptions and beliefs so that the risk of experiencing spiritual distress. Adaptive coping is needed to improve the spiritual well being so that patients more adaptive and have a good quality of life. The purpose of this study was to determine the effect of mindfulness based spiritual to spiritual well being on breast cancer patients undergoing chemotherapy. The study used pilot study with pre and post-test design, with purposive sampling techniques. Total sample 12 breast cancer moslem patients undergoing chemotherapy <3 months. Measurement of spiritual well-being using Spiritual Well Being Scale (SWBS). Data analysis used Paired T-Test. The results showed there was significant efect of mindfulness based spiritual to improve spiritual well being (p-value 0,001). Mindfulness based spiritual can improve the spiritual well being of breast cancer patients undergoing chemotherapy. The recommendation of this pilot study needs to be carried out research with a larger number of samples and analyzed the factors that can improve the spiritual well being of breast cancer patients.